2016
DOI: 10.1007/s00438-016-1194-z
|View full text |Cite
|
Sign up to set email alerts
|

RUDI, a short interspersed element of the V-SINE superfamily widespread in molluscan genomes

Abstract: Short interspersed elements (SINEs) are non-autonomous retrotransposons that are widespread in eukaryotic genomes. They exhibit a chimeric sequence structure consisting of a small RNA-related head, an anonymous body and an AT-rich tail. Although their turnover and de novo emergence is rapid, some SINE elements found in distantly related species retain similarity in certain core segments (or highly conserved domains, HCD). We have characterized a new SINE element named RUDI in the bivalve molluscs Ruditapes dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(78 reference statements)
0
16
0
Order By: Relevance
“…Fragment D12 (Fig. 1b) harbors one complete DTHS3 monomer which has been split by the insertion of a full-length copy of the SINE element RUDI [44]. Although it was previously reported that RUDI regularly forms TSD sequences upon insertion, they were not found in this case.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Fragment D12 (Fig. 1b) harbors one complete DTHS3 monomer which has been split by the insertion of a full-length copy of the SINE element RUDI [44]. Although it was previously reported that RUDI regularly forms TSD sequences upon insertion, they were not found in this case.…”
Section: Resultsmentioning
confidence: 79%
“…TE-related sequences mostly appear as short segments (44–192 bp) of moderate similarity (between 66% and 84%) to DNA transposons and/or LTR-retrotransposons. An exception is the recently characterized short interspersed element (SINE) named RUDI [44], present as a complete copy in D12. In addition, a search for uncharacterized repeated elements by comparing all sequenced fragments revealed two putative MITEs in D. trunculus , DTCM1 and DTCM2, preliminarily classified based on terminal inverted repeats and target site duplication (TSD).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore propose to rename it as the “Cega” (cephalopod + gastropod) domain. Overall, our study enables a wider and more complete picture of HCD distribution than before ( Gilbert and Labuda 1999 , 2000 ; Ogiwara et al 2002 ; Nishihara et al 2006 , 2016 ; Akasaki et al 2010 ; Piskurek and Jackson 2011 ; Luchetti and Mantovani 2013a ; Luchetti et al 2016 ; Matetovici et al 2016 ).…”
Section: Discussionmentioning
confidence: 85%
“…Few examples of SINE horizontal transfer have yet been suggested: the SmaI family in coregonid and salmonid fishes ( Hamada et al 1997 ), a SINE shared by reptiles and mammals ( Piskurek and Okada 2007 ), and a RUDI subfamily between distantly related bivalve species ( Luchetti et al 2016 ). We found that Nin and V domain divergence showed a positive correlation with host species split ages, with few deviations suggesting horizontal transfers and/or paralogous lineage comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation